PENGUJIAN KEKUATAN TARIK DAN KEKUATAN LENTUR KOMPOSIT HIBRID PLASTIK BEKAS KEMASAN GELAS JENIS POLIPROPILENA/ SERBUK KAYU KELAPA TERMODIFIKASI/SERBUK SERAT KACA TIPE E - Silvia, Castiqliana, Halimatuddahliana (Universitas Sumatera Utara, 2015)
This study was aimed to investigate the effect of modified coconut wood flour and maleic anhydride-g-polypropylene addition in tensile strength and flexural strength of hybrid composite. Modification of coconut wood flour was also done to reduce the polarity. The hybrid composites were prepared by mixing method into an extruder. Glass Fiber Flour and maleic anhydride-g-polypropylene composition were made constant at 10 wt.% and 2 wt.% respectively and modified coconut wood flour composition was varied from 10 - 40 wt.%. Tensile test and flexural test were done. The results showed that addition of 20 wt.% modified coconut wood flour had given maximum tensile strength of 24,1 MPa and addition of 30 wt.% modified coconut wood flour had given maximum flexural strength of 31,2 MPa also inclination of both tensile and flexural strength of hybrid composite using maleic anhydride-g-polypropylene.